Strategic Integration of Customer Relationship Management Across Entrepreneurship, Marketing, and Human Resource Management: A PRISMA-Based Systematic Literature Review - Princhita Nabila Maram Pahlawan; Nurendah Shinta Rachmawati; Dea Delia Lestari; Risty Rahma Dafina; Ratna Arista Dewi (Journal Of Marketing and Technology Management, 2025)
The rapid shift toward a Total Experience strategy in the 2025 digital landscape has repositioned Customer Relationship Management as a core organizational infrastructure. This research evaluated how managerial adoption served as a strategic integration between advanced Artificial Intelligence (AI) capabilities and leadership readiness by synchronizing marketing, entrepreneurship, and human resource management. A systematic literature review was performed using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guideline, which involved an in-depth analysis of sixteen selected articles from high-impact databases. The results indicated that effective management of customer-centric data significantly predicted long-term scalability and reduced customer acquisition costs by approximately 22%. Furthermore, the integration of internal relationship management practices was shown to increase employee engagement scores by fifteen points. It was concluded that Customer Relationship Management is a vital mechanism for agile pivoting and opportunity recognition across all organizational domains. This study recommended that leaders prioritize cultural synergy and digital literacy over mere technology procurement to navigate evolving privacy mandates effectively. These findings also suggested that the realization of technical potential remained a byproduct of human-centric factors and managerial foresight.